2020
DOI: 10.6007/ijarbss/v10-i4/7120
|View full text |Cite
|
Sign up to set email alerts
|

Determinant Factors for Employee Retention: Should I Stay?

Abstract: Many organizations are interested in succesion planning in developing their talent. However, there are some challenges in practically implement the planning in talent development process. For instance, one of the most challenging issues in human resource management is dealing with employee turnover, retention and engagement. As high turnover employee is a bad sign as it will increase organization overall cost and time spending to train the new employees. So, these issues need serious attention from the organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 15 publications
2
26
0
1
Order By: Relevance
“…The process in employee retention refers to the policies and practices that businesses use to keep important employees from leaving, including taking steps to encourage employees to stay with the company for as long as feasible (Baharin and Hanafi, 2018 ). Many companies nowadays are looking at employee retention measures by reaching out to their employees to ensure their job satisfaction and keep them at the company for as long as possible (Mahadi et al, 2020 ). This is linked to the company's attempts to help its employees, evidenced by the number of people who leave or join the organization (Tian et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The process in employee retention refers to the policies and practices that businesses use to keep important employees from leaving, including taking steps to encourage employees to stay with the company for as long as feasible (Baharin and Hanafi, 2018 ). Many companies nowadays are looking at employee retention measures by reaching out to their employees to ensure their job satisfaction and keep them at the company for as long as possible (Mahadi et al, 2020 ). This is linked to the company's attempts to help its employees, evidenced by the number of people who leave or join the organization (Tian et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study also explored these factors are independent and significant with medium to large effect size predicting retention tendency. When the age of employees increases (Mahadi et al , 2020), they are emotionally and socially getting connected with co-workers and with the workplace. They will not switch over the workplaces (T.F.…”
Section: Resultsmentioning
confidence: 99%
“…Sen and Bhattacharya (2019) recommended the need for an innovative and global approach to tackle human resource shortage, talent development and retention issues in the Indian service sector. In the study of Mercer Webcast Series – 2016, Mahadi et al (2020) identified the employee voluntary turnover rate is 9.1% globally, and around 15% turnover rate was found in countries like Indonesia, Philippines, Argentina and Romania. Because of skilled labour shortages in the health-care sector, employees expect more financial and non-financial benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Jarak tempat tinggal memengaruhi krusial secara negatif bagi loyalitas tenaga kerja, dibuktikan oleh beberapa kajian. Pertama, kajian milik Mahadi dan kawan-kawan pada tahun 2020, hasil kajian itu mendapati bila Jarak dari rumah ke kantor memengaruhi kepuasan dan loyalitas karyawan (Mahadi, Woo, Baskaran, & Yaakop, 2020). Penelitian kedua dilakukan oleh Demiral pada tahun 2018 terhadap 214 orang karyawan yang berasal dari 29 perusahaan di Turki, hasil dari penelitian tersebut membuktikan bahwa jarak tempat tinggal memengaruhi keinginan karyawan untuk keluar, yang menandakan adanya tingkat loyalitas yang rendah (Demiral, 2018).…”
Section: Jarak Tempat Tinggal (X3) Mempengaruhi Loyalitas (Z)unclassified